Atividade antioxidante do e-1,1-metiltio-selenofenil-2-pirrolidinona-hepteno: um composto orgânico de selênio com baixa toxicidade - Ineu, Rafael Porto (2007)
The objective of this work was to evaluate the antioxidant activity of (E)-1-(1-(methylthio)-1-selenopheny) hept-1-en-2-yl) pyrrolidin-2-one: an organoselenium compound with low toxicity (compound 1). A number of parameters were examined in brain, liver and plasma of rats and mice as indicators of toxicity, including reactive species to the thiobarbituric acid levels, ascorbic acid content, δ-aminolevulinate dehydratase and catalase activity, AST, ALT, urea and creatinine levels. Ours experiments demonstrated that in vitro, compound 1 showed a concentration-dependent reduction in TBARS production and in the generation of reactive species (RS) caused by Fe2+/malonate when was tested by DCFH-DA oxidation. The LD50 for compound 1 was calculated administering by oral route and the results demonstrated higher than 500 mg/kg. We also examined the toxicity of the compound 1 in ex vivo experiments and the results demonstrated that it did not change hepatic δ-aminolevulinate dehydratase activity at 100 and 250 mg/kg only showed an inhibition at the highest dose (500mg/kg) of compound 1 but in this same dosage no significant differences were detected in brain of mice. Hepatic lipid peroxidation in treated mice did not differ from control values otherwise, in brain tissue, all doses showed a significant reduction in TBARS levels. One of the biochemicals parameters measured were urea and creatinine levels in plasma of treated mice treated. The urea levels showed a decrease at highest dose and creatinine to increase at middle and high doses. Ascorbic acid content, that is an endogenous antioxidant, was increased only at the highest dose of compound 1. Catalase activity in brain of exposed mice had a tendency to decrease and showed a significant result only at 100mg/kg. In contrast with this, in hepatic tissue, the catalase activity showed a significant increased in all doses. We concluded that this is a promising compound with greater antioxidant activity and low toxicity but are necessary many detailed pharmacological studies involving this type of organoselenium compounds.